Effects of Ni and Pd metals catalyst on Gamma Alumina support - Yaakob, Zahira; Yosfiah, M. R.; Minggu, Lorna Effery; Ibrahim, M. A.; Daud, W. R. W. (2006)
Catalysts containing Ni or combinations of Pd, Cu and Zn on gamma alumina support have been developed for testing in autothermal methanol reforming reaction. The hydrogen produced by the catalytic reforming of methanol is targeted to be used as a feed for fuel cell. The reaction for reforming of methanol can be performed at low temperature and pressure in the presence of catalysts with high yield and low CO. The calcined catalysts has been characterized by Brunauer, Emmett and Teller (BET) for surface area, Scanning Electron Microscopy (SEM) for shape and dispersion of metals, Powder X-ray diffraction (XRD) for species present and degree of crystallinity and Temperature Programmed Reduction (TPR) for reducible species presence, their interaction and degree of reducibility. The catalyst has specific characteristic in physical and chemical properties due to the location of Ni metal on the surface of the ?-Al2O3. The effects could be observed in colour, SEM, and the total number of pores of the catalyst. The amount of metal in the supporting material ?-Al2O3 also influenced the physical properties of the catalysts. From the catalyst produced with various concentration, it is found that the content of Ni metal with specific amount, fill the channels on the surface of supporting material ?-Al2O3. Based on the catalyst activities data, suitable catalyst to produced hydrogen can be formulated.